Influence of a slow-start on overall performance and running kinematics during 6-h ultramarathon races. Issue 3 (15th March 2020) - Matta, Guilherme G.; Bossi, Arthur H.; Millet, Guillaume Y.; Lima, Pedro; Lima, Jorge P. de; Hopker, James G.
Abstract: The aim of this study was to describe the pacing during a 6-h ultramarathon (race 1) and to investigate whether a slow-start affects performance, running kinematic changes, ratings of perceived exertion (RPE) and fatigue (ROF) (race 2). After a critical speed test, participants completed two 6-h ultramarathons. Race 1 ( n = 16) was self-paced, whereas in race 2 ( n = 10), athletes performed the initial 36 min at speeds 18% below the mean speed of the initial 36 min of race 1. In race 1, participants adopted an inverse sigmoid pacing. Contact times increased after 1 h, and flight times decreased after 30 min (all P ≤ .009); stride length reduced after 1 h 30 min (all P = .022), and stride frequency did not change. Despite the lower speeds during the first 10% of race 2, and higher speeds at 50% and 90%, performance remained unchanged (57.5 ± 10.2 vs. 56.3 ± 8.5 km; P = .298). However, RPE and ROF were lowered for most of race 2 duration (all P < .001). For the comparison of kinematic variables between races, data were normalised by absolute running speed at each time point from 1 h onwards. No differences were found for any of the kinematic variables. In conclusion, decreasing initial speed minimises RPE and ROF, but does not necessarily affect performance. In addition, running kinematic changes do not seem to be affected by pacing manipulation.